Correlation of Serum Insulin-like Growth Factor 1 with Prostate Cancer - Mohsen Ayati (Middle East Journal of Cancer, 2012)
Background: Insulin-like growth factor-1 can act in both an autocrine and paracrine manner to promote normal growth and malignant cellular proliferation. The importance of this factor as a major regulatory peptide has been established for cells, in vitro and in vivo. However, the role of serum insulin-like growth factor-1 levels in the etiology of benign prostatic hyperplasia and prostate cancer has not received sufficient attention. The aim of this study was to determine the relationship between benign prostatic hyperplasia, prostate cancer, and serum insulin-like growth factor-1 levels.Methods: We collected blood samples from 68 individuals with prostate cancer (cases) and 68 individuals with benign prostatic hyperplasia (controls) who were patients at Imam Khomeini Hospital in Tehran, Iran. Those with benign prostatic hyperplasia had normal prostatic specific antigen levels <4 ng/ml and normal prostate according to digital rectal examination. The case group was selected from patientswith pathologically confirmed prostate cancer. Insulin-like growth factor-1 concentrations were measured by a radio immunoassay kit. We used the t-test to compare insulin-like growth factor-1 levels between groups.Results: Patients in the prostate cancer group had a mean age of 68 years, whereas those with benign prostatic hyperplasia had a mean age of 65 years (P>0.05). Mean serum insulin-like growth factor-1 levels were 219 ng/ml for the case group and 133 ng/ml for the control group, which was significant (P=0.0009). We did not observe any correlation between age and insulin-like growth factor-1 in the case group (P=0.83, r= -0.47), however there was a significant correlation in the control group (P=0.007, r=0.549). Although correlation between prostate volume and serum insulin-like growth factor-1 levels was not statistically significant in the case group (P=0.38, r=0.213), therewas a positive correlation observed in the control group (P<0.008, r=0.537).Conclusion: Our findings suggest that insulin-like growth factor-1 may have an etiologic role in prostate cancer. This interpretation is strengthened by the significant difference observed between serum insulin-like growth factor-1 levels in benign prostatic hyperplasia and prostate cancer patients. These results also offer additional opportunities for evaluating patients who have abnormal digital rectal exams or prostate specific antigen levels, yet their biopsies are normal. Under these circumstances, measurement of serum insulin-like growth factor-1 may assist with the decision for a second biopsy.